Peningkatan Daya Saing UMKM Melalui Digitalisasi dan Inovasi Packaging: Studi Kasus pada UMKM UP2K Unyur Makmur, Serang – Banten - Santi Octaviani; Nikke Yusnita Mahardini; Kodriyah Kodriyah; Denny Putri Hapsari; Nana Umdiana; Dilla Fitriana Putri Igefar (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
This community service activity aims to improve the competitiveness of Micro, Small and Medium Enterprises (MSMEs) UP2K Unyur Makmur in Unyur Village, Serang City, Banten through the application of digitalisation and product packaging innovation. The main problems faced by partners are limitations in the use of digital technology for marketing and packaging designs that are unattractive and do not reflect the identity of local products. The methods used in this activity include socialisation, training, mentoring, and evaluation of the implementation of digital marketing strategies and packaging design development. The results of this activity show an increase in the ability of MSME actors to use digital media such as marketplaces, social media marketing, and simple graphic design for product promotion. In addition, the packaging innovations introduced were able to increase the aesthetic value and appeal of products in the eyes of consumers. The tangible impact of this activity was an increase in MSME actors' awareness of the importance of digitalisation and packaging innovation in expanding markets and strengthening brand image. This activity is expected to become a model for digital and creative MSME empowerment in the Serang area and its surroundings.